EFEKTIFITAS PELATIHAN PENGUSAHA UMKM BIDANG MAKANAN DAN MINUMAN DI KOTA DUMAI - Vicy Andriany (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2022)
Micro, small and medium enterprises (MSMEs) in the processed food and beverage sector increasing rapidly in Dumai has inadequate standards for consumers. So that the Dumai City Cooperative and SME Industry Service carries out coaching. The purpose of this study was to determine the training provided to MSME actors and to determine the effectiveness of the training that had been carried out by the Dumai City Cooperative and SME Industry Service. The type of research used is field research with a qualitative descriptive approach. Data collection techniques used in this study are interviews and documentation. The results of the study concluded that the MSME entrepreneur training carried out by the Dumai City Industry, Cooperatives and SMEs Service was through training such as packaging, socialization such as seminars, briefings such as business management, capital and business licensing, as well as providing MSME opportunities to be able to participate in exhibitions in every event. events held in Dumai City and outside the city. Meanwhile, the effectiveness of fostering micro, small and medium enterprises by the Department of Industry, Cooperatives and SMEs of Dumai City to 8 micro, small and medium enterprises has been effective